A 37-year observation of mortality in Chinese chrysotile asbestos workers. Issue 2 (21st September 2011) - Wang, Xiaorong; Yano, Eiji; Qiu, Hong; Yu, Ignatius; Courtice, Midori N; Tse, L A; Lin, Sihao; Wang, Mianzhen
Abstract : Objectives: This 37-year prospective cohort study was undertaken to provide additional evidence for mortality risks associated with exposure to chrysotile asbestos. Methods: 577 asbestos workers and 435 control workers in original cohorts were followed from 1972 to 2008, achieving a follow-up rate of 99% and 73%, respectively. Morality rates were determined based on person-years of observation. Cox proportional hazard models were constructed to estimate HRs of cause-specific mortality, while taking into account age, smoking and asbestos exposure level. Results: There were 259 (45%) deaths identified in the asbestos cohort, and 96 died of all cancers. Lung cancer (n=53) and non-malignant respiratory diseases (n=81) were major cause-specific deaths, in contrast to nine lung cancers and 11 respiratory diseases in the controls. Age and smoking-adjusted HRs for mortality by all causes and all cancers in asbestos workers were 2.05 (95% CI 1.56 to 2.68) and 1.89 (1.25 to 2.87), respectively. The risks for lung cancer and respiratory disease deaths in asbestos workers were over threefold that in the controls (HR 3.31(95% CI 1.60 to 6.87); HR 3.23 (95% CI 1.68 to 6.22), respectively). There was a clear exposure–response trend with asbestos exposure level and lung cancer mortality in both smokers and non-smokers. Conclusion: Data from this prospective cohort provide strong evidence for increased mortality risks, particularly from lung cancer and non-malignant respiratory diseases, associated with exposure to chrysotile asbestos, while taking into account of the smoking effect.